Tax Policy Solutions for Economic Growth in Ho Chi Minh City - Duc, Luong Minh (Journal of Business Management and Economic Development, 2025)
This research examines tax policy strategies to enhance sustainable economic development in Ho Chi Minh City, Vietnam. Using a qualitative research approach, the study identifies inefficiencies in tax collection, the impact of tax incentives, and issues related to governance and compliance. Key findings highlight the need to align local tax policies with national economic strategies, increase transparency, and optimize tax incentives to foster economic stability. Recommendations focus on enhancing digital tax systems, improving public tax awareness, and reforming bureaucratic processes to establish a more efficient and equitable tax framework.